Molecular detection of tick-borne haemoparasites in cattle and buffalo samples from Mashonaland West and Masvingo Provinces, Zimbabwe - Sibeko-Matjila, K.P. (Kgomotso Penelope) (University of Pretoria, 2024)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.